An overview of the economy of Kazakhstan: development trends between 2008-2022 - Sarkambayeva , Sh.G.; Sailaubekov , N.T.; Mynzhanova , G.T.; Vasa, L. (Journal of Economic Research & Business Administration, 2025)
This study aims to provide a comprehensive understanding of Kazakhstan’s economy at present and review the changes that have occurred over the period from 2008 to 2022. To capture the key macroeconomic aspects, the dynamics and directions of significant indicators for long-term economic growth were examined, including overall economic productivity, employment structure, and real output. The study used analytical methods that include trend analysis, structural analysis, comparative analysis (pre/post analysis), descriptive statistics methods, correlation and regression analysis, as well as theoretical provisions of macroeconomics. Statistical data published by the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan, the National Bank of the Republic of Kazakhstan and international organizations were used. Thus, the purpose of this study is to review the economy of Kazakhstan, and the result is to identify trends in economic development in the period from 2008 to 2022. The results obtained during the study allowed us to draw the following conclusions: the share of the labor force among the population is decreasing and leads to slow economic growth, household incomes and investment opportunities remain quite low, and solving the country’s economic security issues is hampered by lopsided exports and inelastic import demand. The results of the conducted research can be useful in the practical activities of government agencies involved in strategic development planning of the Republic of Kazakhstan. Key words: Real GDP, employment, productivity, population income, development trends.